Maternal smoking during pregnancy and cord blood DNA methylation: new insight on sex differences and effect modification by maternal folate levels. Issue 5 (4th May 2018) - Zhang, Boyang; Hong, Xiumei; Ji, Hongkai; Tang, Wan-yee; Kimmel, Mary; Ji, Yuelong; Pearson, Colleen; Zuckerman, Barry; Surkan, Pamela J.; Wang, Xiaobin
ABSTRACT: Maternal smoking during pregnancy may affect newborn DNA methylation (DNAm). However, little is known about how these associations vary by a newborn's sex and/or maternal nutrition. To fill in this research gap, we investigated epigenome-wide DNAm associations with maternal smoking during pregnancy in African American mother-newborn pairs. DNAm profiling in cord (n = 379) and maternal blood (n = 300) were performed using the Illumina HumanMethylation450 BeadChip array. We identified 12 CpG sites whose DNAm levels in cord blood were associated with maternal smoking, at a false discovery rate <5%. The identified associations in the GFI1 gene were more pronounced in male newborns than in females ( P  = 0.002 for maternal smoking × sex interaction at cg18146737). We further observed that maternal smoking and folate level may interactively affect cord blood DNAm level at cg05575921 in the AHRR gene ( P  = 5.0 × 10 −4 for interaction): compared to newborns unexposed to maternal smoking and with a high maternal folate level (>19.2 nmol/L), the DNAm level was about 0.03 lower ( P  = 3.6 × 10 −4 ) in exposed newborns with a high maternal folate level, but was 0.08 lower ( P  = 1.2 × 10 −8 ) in exposed newborns with a low maternal folate level. Our data suggest that adequate maternal folate levels may partly counteract the impact of maternal smoking on DNAm. These findings may open new avenues of inquiry regarding sex differences in response to environmental insults and novel strategies to mitigate their intergenerational health effects through optimization of maternal nutrition.